Implementation of 2013 curriculum in history learning - Rampun, Gina Julyesta; Bahri (International Journal of Curriculum Development, Teaching and Learning Innovation, 2025)
The purpose of this study is to analyze the content of history lessons in the 2013 curriculum for the Senior High School level or equivalent and understand the role of historical studies as an important part of the 2013 curriculum. The method used in this research is library research, which not only searches for sources relevant to the research topic, but also collects data for writing. The results of the research show that history has two main branches in Indonesian history (compulsory) which is followed by all specialization majors (IPA and IPS), as well as the specialization history branch (IPS) which has a broader scope. Both groups of history, compulsory and specialization, in the development of competency standards in the previous curriculum, have become core competencies that show an increase in the goal of achieving competence